ENVELOPE PROTEIN DOMAIN III (ED III) DETECTION BASED ON SURFACE-ENHANCED RAMAN SCATTERING FOR DENGUE FEVER DIAGNOSE - Novaznursyah Costrada, Aldo
Surface-enhanced Raman Scattering (SERS) based ED III protein detection has been conducted as a dengue virus diagnosis. ED III is one of the ectodomains of the envelope located along the surface of the dengue virus and acts as a receptor for the virus with its host cells. The SERS substrate used in this study is On-Spec-lite SERS by NECTEC and fabricated as a grating surface coated with gold nanoparticles using ion sputtering. Simulations to observe the effect of radius and distance between gold nanoparticles struck by incident light with Raman wavelength (785 nm) were also carried out using COMSOL. Based on the research that has been done, the simulation results show that an increase in the electric field occurs if the radius and distance between the nanoparticles are getting smaller. OnSpec-lite SERS has a more significant increase in Raman intensity than the grating-Au surface when detecting ED III using Raman spectroscopy. The amino acids in the ED III Raman bands are Glycine, Alanine, Histidine, and Proline. The highest intensity Raman band that appears is 850 cm-1 . Based on the research done in dengue virus detection, ED III has a typical Raman peak of 850 cm-1 which is the Raman band of Glycine, Histidine, and Alanine with CCN symmetry stretching vibration mode (v(CCN)). This distinctive characteristic of ED III can be used as a diagnostic to detect dengue virus